Prediction of the in-piston-bowl swirl ratio of diesel engines. (September 2019) - Sun, Yanzhe; Wang, Tianyou; Wen, Ming; Li, Yufeng; Tian, Fuquan; Lu, Zhen
Steady flow tests are widely used to evaluate the performance of intake ports in generating swirl flow in diesel engines. Such test data, however, may deviate largely from the real in-piston-bowl swirl ratio due to the complex unsteady air motion in the compression stroke. In this study, a new method is proposed to predict the unsteady in-piston-bowl swirl ratio of diesel engines from steady flow test data by focusing on three key steps, including the swirl field at intake valve close timing, swirl enhancement due to squish flow, and swirl decay during the compression stroke. Experimental results on an optically accessible diesel engine under non-firing conditions show that, at intake valve close, the relationship between the swirl ratio and the vertical location was approximately linear and the mean swirl ratio could be fitted by a Bessel function; the correlation between the swirl decay coefficient and surface-to-volume ratio was built by fitting the experiment data. Furthermore, the in-piston-bowl swirl ratio during the compression stroke could then be derived according to the conservation of angular momentum.